Paramedicine And EMS Networks In Trauma And Anesthesia Care: An Integrated Psychophysiological And Sociological Perspective — A Scoping Review (The Review of Diabetic Studies, 2025)
Background:Paramedicine and emergency medical services (EMS) have become critical contributors to trauma and anesthesia care, yet the literature addressing their integrated clinical, psychophysiological, and sociological roles remains fragmented. Understanding how these factors interact is essential for optimizing preoperative decision-making, airway management, and trauma system performance.Objectives:This scoping review aims to map evidence on how paramedicine and EMS networks contribute to trauma and anesthesia care through clinical interventions, psychophysiological mechanisms, and sociological dynamics across prehospital and hospital settings.Methods:The review followed the Joanna Briggs Institute (JBI) guidelines and the PRISMA-ScR checklist. A comprehensive search was conducted across PubMed, Scopus, Web of Science, CINAHL, EMBASE, PsycINFO, and Sociological Abstracts. Eligible studies included empirical research, reviews, and conceptual papers (2000–2025) addressing EMS involvement in trauma or anesthesia and examining clinical, psychophysiological, or sociological constructs.Results:Findings demonstrate that paramedics significantly influence early trauma and anesthesia outcomes through advanced airway management, hemorrhage control, analgesia, and structured triage. Psychophysiological factors—such as stress, cognitive load, and situational awareness—were strongly associated with decision-making accuracy and procedural performance. Sociological determinants, including teamwork, communication quality, hierarchy, and organizational culture, shaped the effectiveness of EMS–hospital transitions and perioperative coordination. Integrated trauma systems with formal EMS–anesthesia pathways showed improved readiness and reduced perioperative delays.Conclusion:Trauma and anesthesia care are governed by an interplay of clinical expertise, human-factor physiology, and sociological structures. Paramedicine serves as the foundational link in this continuum, influencing both immediate interventions and downstream surgical planning. Strengthening interdisciplinary communication, enhancing stress-management and clinical training, and embedding EMS roles within trauma–anesthesia pathways may improve patient outcomes and system efficiency.